A novel strategy for in vivo angiogenesis and osteogenesis: magnetic micro-movement in a bone scaffold. (5th November 2018) - Luo, Cong; Yang, Xiaolan; Li, Ming; Huang, Hua; Kang, Quan; Zhang, Xiaobo; Hui, Hui; Zhang, Xin; Cen, Chaode; Luo, Yujia; Xie, Lina; Wang, Changxuan; et al.
Abstract: Angiogenesis and osteogenesis in tissue-engineered bone are the key factors in the clinical application of tissue-engineering technology to repair large bone defects. In vivo cells that are farther than 200 μm from capillaries cannot survive due to lack of nutrients and oxygen, and thus, the tissue-engineered bone is not suitable for repairing large bone defects. In this study, we constructed a novel artificial bone scaffold loaded with superparamagnetic plasmid gene microspheres. Magnetic micro-movement of the magnetic microspheres in the scaffold was generated by an oscillating magnetic field and a static magnetic field to promote the release of plasmid genes from microspheres for transfection of surrounding cells, resulting in protein expression of vascular endothelial growth factor, thus promoting angiogenesis and osteogenesis in the scaffold, internal vascularization of the artificial bone scaffold and repair of large bone defects.